Development of a ChemSketch-Integrated Flipbook to Enhance Students’ Conceptual Understanding of Functional Groups in Organic Compounds - Ilham, Muhammad; Munawwarah, Munawwarah; Ilmi, Nurul; Nurtaqwa, Nurtaqwa; Ramadhani, St. Rahayu (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This study aimed to develop a ChemSketch-integrated flipbook as a digital teaching material for the topic of functional groups of carbon compounds, given that chemistry learning frequently involves abstract concepts that are difficult for students to comprehend through conventional instruction alone. The study employed a Research and Development approach using the DDD-E model, which includes the stages of decide, design, development, and evaluate. The participants were 21 twelfth-grade students, while product validation was conducted by six experts consisting of two media experts, two material experts, and two language experts. Data were collected through validation sheets and student response questionnaires, then analyzed descriptively using percentage-based feasibility criteria. The findings revealed that the developed teaching material achieved a validity score of 89% in the media aspect, 90.5% in the material aspect, and 75% in the language aspect, indicating that it was feasible for classroom use. Student responses were predominantly positive, particularly regarding the suitability of the media for learning, its contribution to learning motivation, and its support in facilitating the understanding of functional group concepts. The novelty of this study lies in the direct integration of ChemSketch-generated two-dimensional and three-dimensional molecular visualizations into a flipbook, allowing the material to function not only as a digital text but also as a representational learning tool. These findings suggest that the developed flipbook is feasible, well-received by students, and has the potential to support conceptual understanding and student engagement in chemistry learning.